Bravi Riccardo. An excursus on truth and language in Paul Celan - Bravi Riccardo (Philological Treatises, 2020)
The article aims at giving an overview of the complex relation between truth and language in Paul Celan, poet and translator born in 1920 in Chernovtsy (Rumanian territory à l’époque – nowadays Ukraine). If German language was at the same time mother tongue of the poet (in heritage from his mother’s side) used to establish an autonomous poetical corpus and starting point for translating other languages, then it was also the idiom spoken by the Nazis who disseminated death all over Europe killing the most important person in poet’s life. The paper deals with this continuous research on the limits of language, willing to find a sort of reality located beyond something yet impossible to pronounce – especially after Auschwitz, the destruction of European Jewry. At this point, Celan’s messianism has been recognized as an important aspect of this process thus guiding the essay to some theoretical hypothesis.